Towards design strategies for anion–π interactions in crystal engineering. Issue 1 (20th October 2015) - Bauzá, Antonio; Mooibroek, Tiddo J.; Frontera, Antonio
Abstract : This highlight article summarizes some of the fundamental aspects of the anion–π interaction leading to several design strategies for generating it in solids. In the main body we highlight some relevant examples that illustrate the viability of these strategies and the importance of anion–π interactions in crystal engineering. Abstract : For well over half a century part of the scientific community has been committed to understanding and predicting how molecules recognize each other. This subject of unceasing interest, 'supramolecular chemistry', relies on the understanding of noncovalent interactions. Among the noncovalent forces, the anion–π interaction has attracted increasing attention ever since its inception about two decades ago. This highlight article first summarizes some of the fundamental aspects of this interaction leading to several design strategies. In the main body we highlight some relevant examples that illustrate the viability of these strategies and the importance of anion–π interactions in crystal engineering.